2021
DOI: 10.3390/ijms23010089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Iron Chelators on the Biology of Cancer Stem Cells

Abstract: Neoplastic diseases are still a major medical challenge, requiring a constant search for new therapeutic options. A serious problem of many cancers is resistance to anticancer drugs and disease progression in metastases or local recurrence. These characteristics of cancer cells may be related to the specific properties of cancer stem cells (CSC). CSCs are involved in inhibiting cells’ maturation, which is essential for maintaining their self-renewal capacity and pluripotency. They show increased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…MAPK/ERK signaling activated ferritin and regulated NCAO4-mediated iron phagocytosis and HO1 expression, which provided potential therapeutic targets for AKI management ( Su et al, 2019 ). Deferiprone has been used in patients with high ferrous load from repeated transfusions, but there have been no studies related to the application of deferiprone for the prevention or treatment of AKI due to rhabdomyolysis ( Szymonik et al, 2021 ). Baicalein, an important active ingredient in the Chinese herb Scutellaria baicalensis, attenuated myocardial ischemia-reperfusion-induced AKI by regulating the B-cell lymphoma-2 (BCL2), extracellular signal-regulated kinase 1/2, and BCL2 associated X (BAX) activation of protein kinase B (PKB) ( Lai et al, 2016 ; Szymonik et al, 2021 ).…”
Section: Treatment Of Ferroptosis In Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK/ERK signaling activated ferritin and regulated NCAO4-mediated iron phagocytosis and HO1 expression, which provided potential therapeutic targets for AKI management ( Su et al, 2019 ). Deferiprone has been used in patients with high ferrous load from repeated transfusions, but there have been no studies related to the application of deferiprone for the prevention or treatment of AKI due to rhabdomyolysis ( Szymonik et al, 2021 ). Baicalein, an important active ingredient in the Chinese herb Scutellaria baicalensis, attenuated myocardial ischemia-reperfusion-induced AKI by regulating the B-cell lymphoma-2 (BCL2), extracellular signal-regulated kinase 1/2, and BCL2 associated X (BAX) activation of protein kinase B (PKB) ( Lai et al, 2016 ; Szymonik et al, 2021 ).…”
Section: Treatment Of Ferroptosis In Acute Kidney Injurymentioning
confidence: 99%
“…Deferiprone has been used in patients with high ferrous load from repeated transfusions, but there have been no studies related to the application of deferiprone for the prevention or treatment of AKI due to rhabdomyolysis ( Szymonik et al, 2021 ). Baicalein, an important active ingredient in the Chinese herb Scutellaria baicalensis, attenuated myocardial ischemia-reperfusion-induced AKI by regulating the B-cell lymphoma-2 (BCL2), extracellular signal-regulated kinase 1/2, and BCL2 associated X (BAX) activation of protein kinase B (PKB) ( Lai et al, 2016 ; Szymonik et al, 2021 ). It has been shown that baicalein can also enhance cellular resistance to ferroptosis by limiting iron accumulation and lipid peroxidation in cells, which makes it a promising therapeutic agent for ferroptosis-related tissue damage ( Xie et al, 2016b ).…”
Section: Treatment Of Ferroptosis In Acute Kidney Injurymentioning
confidence: 99%
“…A truncated isoform of NDRG1 has been observed in prostate cancer cell lines but not normal cell lines, this could explain Frontiers in Molecular Biosciences frontiersin.org the contradictory roles observed in cells, the full length isoform may be responsible for the tumour suppressor roles of NDRG1 and the truncated version for the oncogenic roles, this warrants further investigation (Park et al, 2018). In addition to NDRG1 upregulation, iron chelation can inhibit cancer cell stemness (Szymonik et al, 2021). Cancer stem cells present a roadblock to full patient recovery as their capacity for self-renewal can fuel metastasis and drug resistance (Yu et al, 2012b;Szymonik et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have found that the inevitability of treatment resistance and recurrence in GBM may be due to the presence of cancer stem-like cells (CSCs) ( 32 ). Owing to the nature of enhanced resistance to conventional chemo/radiotherapy and metastasis, CSCs have been proposed as promising targets for cancer eradication ( 33 ).…”
Section: Regulation Of Ferroptosis In Gliomamentioning
confidence: 99%
“…This alteration in iron metabolism is likely to be related to the treatment resistance of GBM CSCs. Expression of stemness-related markers has been proven to be affected by iron chelators, therefore targeting iron metabolic processes in CSCs is promising for reducing tumor cell therapeutic resistance ( 32 ).…”
Section: Regulation Of Ferroptosis In Gliomamentioning
confidence: 99%